HUBUNGAN GAYA KEPEMIMPINAN DAN MOTIVASI DENGAN KINERJA PEGAWAI DI BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI JAWA TENGAH - Rike Dewi Puspitasari; Herbasuki Nurcahyanto; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
In any organization man holding a very important role. Humans can said force middlemost as an engine of an organization organizations, to accomplish a purpose where supported with human resource quality. Performance bpbd central java provinces less than optimal, because human resources and the less employees still lacking conformity with capability owned thus causing the low in resolving their jobs.Research purposes to test the relation between a style of leadership and motivation with the performance of employees, both in partial and simultaneous. Type this research using eksplanatori with a sample of 62 people by the use of sampling saturates. Engineering analysis used is a technique analysis rank kendall and concordance kendall, used to know the whereabouts the relations between variables.The result showed that. The employee performance disaster management agency of the province of central java overall good likewise with motivation work civil servants who are high but the style of leadership is not appropriate because the rates of ripeness employees were heading high but orientation duty high and orientation relations low. The results of the test hypotheses indicates that there is a relationship between the style of leadership by the employee performance in regional disaster management agency of the province of central java. Shall be proven with a price z-hitung ( 3.52 ) > Zt5% (1,96) and sig of 0,001 < 0.05, there is a relationship between motivation with the performance of employees in regional disaster management agency of the province of central java. Shall be proven with a price z-hitung (2,94) > Zt5% (1,96) and sig of 0,007 < 0.05, there ' s a style of leadership, and motivation employees jointly having relation to the employee performance, can be proven by the test 2 known that the 2h of 72,224 > 2 t5% (43,1).Education and training needs to be done, the delivery of a duty that clear to improve understanding employees against their jobs. Leaders must be willing to listen and receive complaints and advice from employees.. Reviewing the health insurance, and necessary briefing.